The Effects of Dynamic Managerial Capabilities and Transformational Leadership on Firm Performance: The Mediating Roles of Innovative Work Behavior and Competitive Advantage - Imam Sucipto; Tri Wahyu Wirjawan; Ahmad Gunawan; Salsha Nabila (Global Research Collaboration, 2026)
This study examines the effects of Dynamic Managerial Capabilities and Transformational Leadership on Firm Performance through the mediating roles of Innovative Work Behavior and Competitive Advantage. The research was conducted in the Indonesian electronics industry, specifically targeting manufacturing firms. Employing a quantitative survey method, data were collected from 124 managers and employees and analyzed using PLS-SEM with SmartPLS software. The results reveal strong explanatory power, with the model accounting for 75.1% of the variance in Firm Performance (R2 = 0.751). The findings indicate that Transformational Leadership (beta = 0.482) and Dynamic Managerial Capabilities (beta = 0.367) have significant positive effects on Innovative Work Behavior. Furthermore, Innovative Work Behavior significantly drives Competitive Advantage (beta = 0.592) and Firm Performance (beta = 0.568). The direct effects of managerial capability and leadership on firm performance were insignificant, confirming a full mediation mechanism. The study's cross-sectional design and single-industry focus limit generalizability, yet it contributes to Dynamic Capability and Transformational Leadership theories by highlighting that competitiveness is achieved primarily through innovation-based behavioral mechanisms